MiR-155 Promotes ox-LDL-Induced Autophagy in Human Umbilical Vein Endothelial Cells. (4th June 2017) - Zhang, Zhaozhi; Pan, Xudong; Yang, Shaonan; Ma, Aijun; Wang, Kun; Wang, Yuan; Li, Ting; Liu, Shihai
Abstract : As an evolutionarily conserved metabolic process, autophagy is involved in the process of atherosclerosis (AS). MicroRNA-155 (miR-155), a multifunctional miRNA, plays an important role in many physiological and pathological conditions, including AS and autophagy. However, the effect of miR-155 on the regulation of autophagy in endothelial cells has not been reported to date. Therefore, the objective of our study was to investigate the role of miR-155 in autophagy induced by oxidized low-density lipoprotein (ox-LDL) in human umbilical vein endothelial cells (HUVECs). Our results demonstrated that ox-LDL induced autophagy in HUVECs and increased the expression of miR-155 significantly. Overexpression of miR-155 improved autophagic activity, whereas low expression of miR-155 inhibited autophagic activity. Therefore, the data demonstrated that miR-155 has a modulating effect on the autophagy of vascular endothelial cells.